2021
DOI: 10.1016/j.celrep.2021.109305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of presented SARS-CoV-2 HLA class I and HLA class II peptides using HLA peptidomics

Abstract: The human leukocyte antigen (HLA)-bound-viral antigens serve as an immunological signature that can be selectively recognized by T cells. As viruses evolve by acquiring mutations, it is essential to identify a range of viral presented antigens. Utilizing HLA-peptidomics we were able to identify SARS-CoV-2-derived peptides presented by highly prevalent HLA Class-I (HLA-I) molecules using infected cells as well as overexpression of SARS-CoV-2 genes. We found 26 HLA-I peptides and 36 HLA class-II (HLA-II) peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 89 publications
(112 reference statements)
3
55
1
2
Order By: Relevance
“…TGSNVFQTR from spike glycoprotein (638-646) was predicted binding to A*68:01 allele and it locates within the SD1 domain. ITFGGPSDSTGSNQNGER from nucelocapsid protein (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) was also identified in this study and has been predicted to bind to the same allele. Additionally, two class II peptides from nucleocapisd protein SPDDQIGYYRRATRRIR and FSKQLQQSMSSADSTQA were identified, which has not been reported before.…”
Section: Immunopeptidomics Identified Viral Epitopes Presented On Bot...mentioning
confidence: 57%
See 2 more Smart Citations
“…TGSNVFQTR from spike glycoprotein (638-646) was predicted binding to A*68:01 allele and it locates within the SD1 domain. ITFGGPSDSTGSNQNGER from nucelocapsid protein (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) was also identified in this study and has been predicted to bind to the same allele. Additionally, two class II peptides from nucleocapisd protein SPDDQIGYYRRATRRIR and FSKQLQQSMSSADSTQA were identified, which has not been reported before.…”
Section: Immunopeptidomics Identified Viral Epitopes Presented On Bot...mentioning
confidence: 57%
“…Host cells infected by the coronavirus is the simplest model to study the mechanism of viral infection and its impact on the immune system for the development of vaccines and therapeutics. Although several immunopeptidomics and proteomics studies of SARS-Cov-2 infected cells have been reported 19,[23][24][25][26]36 , there is not yet a study that integrated both immunopeptidomics and proteomics, including PTM targeted subomics. Thus, we developed a workflow that included immunopeptidomcis, proteomics, glycoproteomics, phosphoproteomcis and HLA targeted interactomics to provide with a comprehensive overall view of how host cells response to infection that may attribute to the pathology of Covid-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition between innate and adaptive immune response is central to the clinical progression of SARS-CoV-2 infection [10] and the destruction of lung cells triggers a local immune response, recruiting infection-responsive macrophages and monocytes, release cytokines and activate adaptive T-and Bcell immune responses [11] , as well as the release of interleukin (IL)-1β and IL-18, which contribute to the pathogenic inflammation responsible for the severity of COVID-19 symptoms [12] . Viral antigens bound to human leukocyte antigen (HLA) serve as an immune signature that can be selectively recognized by T cells [13] . Protective and harmful HLA variants have been described in both mild and severe forms of the disease, but considering the large number of existing variants, the data collected in such a short time span are to some extent confusing and contradictory [14] .…”
Section: Immune Responsementioning
confidence: 99%
“…Это позволяет выбрать клоны Т-клеток с наиболее желаемыми свойствами и генерировать антиген-специфичные трансгенные Т-клетки [48]. Кроме того, иммунодоминантные пептиды могут быть получены из последовательностей с открытой рамкой считывания, которые не захватываются современными схемами вакцинации [33,49].…”
Section: фенотип и функция Sars-cov-2-специфичных т-клеток анализ мар...unclassified